2000
DOI: 10.1002/1096-9845(200010)29:10<1425::aid-eqe965>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Study on a new shear wall system with shaking table test and finite element analysis

Abstract: SUMMARYA new seismic energy dissipation shear wall structure is proposed in this paper. The new shear wall is one with purposely built-in vertical slits within the wall panel, and rubber belts as seismic energy dissipation devices are installed in the vertical slits. In order to verify this concept, shaking table tests of a 10-storey shear wall model with rubber belts "lled in the vertical slits were carried out, and comparison of seismic behaviour was made between the new shear wall system and a shear wall wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The slit wall showed an increase of the ductility and seismic energy dissipation due to slits and connectors between parts of the wall. Further studies by other researches revealed an increase in the ductility within the slit shear walls in comparison to normal shear walls without undermining of load-bearing resistance [11,12]. Although this technique has been used in shear wall, no report has been found on its use in water tower.…”
Section: Introductionmentioning
confidence: 96%
“…The slit wall showed an increase of the ductility and seismic energy dissipation due to slits and connectors between parts of the wall. Further studies by other researches revealed an increase in the ductility within the slit shear walls in comparison to normal shear walls without undermining of load-bearing resistance [11,12]. Although this technique has been used in shear wall, no report has been found on its use in water tower.…”
Section: Introductionmentioning
confidence: 96%
“…For instance in Bucharest, during the 1977 Vrancea (Romania) earthquake, these buildings showed a high seismic vulnerability: one building with cast in situ reinforced concrete structural walls totally collapsed, seven other buildings suffered partial collapse, 19 were significantly damaged and 72 (Muto et al, 1973), (b) slit panel with strips anchored in beams (Liou and Sheu, 1998), (c) precast panel with strips assembled by post-stressing (Pavlik and Vasionkin, 1976), (d) cast in situ slit wall with a slit zone with short connections (Kwan et al, 1999), (e) cast in situ slit wall with rubber belts inserted in slit zone (Lu and Wu, 2000) and (f) cast in situ reinforced concrete slit walls with a variable number of slits on height (Sabouri and Ziyaeifar, 2009) Reinforced concrete slit walls were moderately damaged. Some of the reasons of the collapses were the inadequate wall density, the inadequate amount and detailing of the wall reinforcement and the lack of confinement in the boundary elements (Bostenaru and Sandu, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Shake table testing on energy dissipation systems includes isolation systems (Villaverde and Mosqueda, 1999;Samali et al, 2003;Dolce et al, 2007), semi-active and passive control of building structures (Sun et al, 2003;Dolce et al, 2005), and structures with viscous dampers Chang et al, 2008). Shake table testing of new types of structures and dams has also increased (Lu and Wu, 2000;Tinawi et al, 2000;Morin et al, 2002;Midorikawa et al, 2006;Wight et al, 2007;Ghaemmaghami and Ghaemian, 2008). For highrise buildings, Li et al (2006) conducted shake table testing of a 1:20 scaled model of a typical reinforced concrete (RC) residential building in Hong Kong, that included a thick transfer plate at the fourth fl oor.…”
Section: Introductionmentioning
confidence: 99%